Assessment approach for multiaxial fatigue damage of deck and U-rib weld in steel bridge decks. (20th November 2018) - Fu, Zhongqiu; Wang, Yixun; Ji, Bohai; Liu, Tianjia
Highlights: An approach for fatigue damage prediction under multiaxial fatigue was proposed. The critical plane approach was introduced to predict the fatigue damage. Multiaxial stress of deck and U-rib welds in different positions was analysed. The rotation angle of the maximum principal stress was calculated. Abstract: Assessment approach for multiaxial fatigue damage of deck and U-rib weld in steel bridge decks was studied. The orthotropic steel bridge deck was modelled to analyse the multiaxial stress state of the weld under wheel load. A multiaxial fatigue loading experiment was carried out to assess the fatigue strength of deck and U-rib weld based on equivalent stress and maximum principal stress. The critical plane approach which is suitable for deck-U rib welds was also established. The assessment results were then compared to those obtained by uniaxial fatigue approach. Reasonable multiaxial fatigue principles were proposed for deck and U-rib welds in different positions. The results show that multiaxial fatigue stress is observed in the deck-U rib weld. The shear stress may exceed normal stress and become the main reason for fatigue damage, thus a multiaxial fatigue approach is necessary for fatigue damage assessment. The nominal stress approach is suggested for fatigue assessment of deck and U-rib weld between diaphragms, which leads to conservative results and is more applicable to engineering practice. The critical plane approach is suggested for fatigue assessment of deck and U-rib weld on the diaphragm considering multiaxial fatigue effects and non-proportional stress in the weld.